Risk Factors in the Progression of Subclinical Atherosclerosis in Women with Systemic Lupus Erythematosus - Lertratanakul, Apinya (2014)
OBJECTIVES: To investigate risk factors in the subclinical atherosclerosis progression as measured by coronary artery calcium (CAC) and aorta calcium (AC) in women with Systemic Lupus Erythematosus (SLE) (cases) and in comparison with a control population. METHODS: A cohort of 149 cases and 124 controls participated in the Study of Lupus Vascular and Bone Long-term Endpoints (SOLVABLE). Demographic information, cardiovascular and SLE risk factors, and laboratory assessments were collected at an initial visit. CAC and AC were measured by electron beam computed tomography (CT) or multi-detector CT at an initial and a follow-up visit. Logistic regression models were used to identify predictors of progression in CAC and AC; multivariate models were adjusted for age, hypertension, and total cholesterol/HDL ratio. RESULTS: Higher modified ACR/SLICC-DI (OR 2.15, 95%CI 1.33–3.57), use of a corticosteroid (OR 2.93, 95%CI 1.14–7.86), and use of aspirin (OR 4.23, 95%CI 1.53–11.74) were associated with CAC progression in multivariate models. Presence of SLE (OR 2.64, 95%CI 1.26–5.72), lower C3 (OR 0.54, 95%CI 0.33–0.87), lower C4 (OR 0.49, 95% CI 0.27–0.86), use of a corticosteroid (OR 2.73, 95%CI 1.03–7.64), higher corticosteroid dose (OR 1.77, 95%CI 1.12–3.00), higher lipoprotein(a) (OR 1.80, 95%CI 1.11–2.98), higher homocysteine (OR 2.06, 95%CI 1.06–4.29) were associated with AC progression in multivariate models. CONCLUSIONS: Higher disease damage at the first study visit, as measured by the modified ACR/SLICC-DI, may predict increased risk in CAC progression, whereas higher disease activity at the first study visit, as measured by hypocomplementemia and use of corticosteroids, may predict increased risk in AC progression.